Zastosowanie metody zerowej użyteczności do szacowania składek w ubezpieczeniach komunikacyjnych OC - Szymańska, Anna (Application of zero-utility method to estimate premiums in civil responsibility car insurance, 2006)
The basis of insurance activity is the correct estimation of insurance premiums. The premiums should be estimated in such away that the insuring company would not incur losses and the insured would not pay too much or too little. The overall premium is the net premium enlarged by the security loading and insurance activity costs. In the paper the zero-utility method is presented. It was also investigated if estimating premiums by means of the method selected allows to build optimal bonus-malus system. The investigation was carried out on real data from a Łodz insurance company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 532-539